Psikoedukasi Bauran sebagai Alternatif Efektif Mengatasi Kecemasan pada Kanker - Andrian Waluya Adi; Agung Waluyo; Dewi Gayatri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine how effective the psychoeducation mix is in reducing anxiety levels in patients with cancer so that it can be used as an effective alternative in reducing the anxiety levels of cancer patients in Indonesia. The research design in this study uses a systematic review. The article search process uses the electronic database Clinicalkey, Scopus, Sage, Science Direct, Proquest, Clinicalkey for nursing, and Taylor, Francis Online, Embase with keywords based on the PICO elements